1980년대와 1990년대 우리나라의 시정 변화 - 김영성; 이시혜; 김진영; 문길주; 김용표 (한국대기환경학회, 2002)
During the past two decades, primary pollutants in the ambient air have been substantially reduced in Korea byaggressive government efforts such as the switchover to clean fuels and equipment of automobiles with a three-way catalytic converter. However, visibility impairment in Seoul and major metropolitan areas has been a stubbornfrom photochemical reactions could contribute to this visibility impairment. In addition, Korea is locateddownwind of the prevailing westerlies from China and is influenced by the emissions of air pollutants in China. Inorder to assess this complicated problem of visibility impairment, the visibility trends for the past 17 yearsgenerally the lowest in the winter morning in comparison with those in the summer afternoon as well as the annualaverage values. It was believed that primary pollution was principally responsible for visibility impairment in mostareas. The visibility in the summer afternoon was lower in clean coastal areas along with a high level of relativehumidity due to the inow of moist air accompanied by sea breeze. Although contributions of secondary particlesfrom photochemical reactions and long-range transport of ne particles to the visibility impairment were probable,their certain evidences were not found.